Catha Edulis Active Principle, Cathinone, Suppresses Motor Coordination, Accelerates Anxiety and Alters the Levels of Dopamine and its Metabolites in the Limbic Areas of Male Swiss Albino Mice - Safhi Mohammed M.; Alam Mohammad Firoz; Khuwaja Gulrana; Hussain Sohail; Siddiqui Mohammed Hakeem; Islam Farah; Khardali Ibrahim; Al-Sanosi Rashad Mohammed; Alhazmi Hassan A.; Khan Andleeb; Islam Fakhrul (Acta Pharmaceutica)
Cathinone, the active principle of khat (Catha edulis), stimulates, excites and produces euphoric feelings in khat users. Locomotor and rearing activities, either individual or in groups, of male Swiss albino mice were decreased significantly compared to the control. Motor coordination tests (rotarod, rope climb and grip tests) have shown decreased motor performance in the mice treated with cathinone compared to the control. The elevated plus maze test has shown significant anxiety in the mice compared to the control. Contents of dopamine and its metabolite, homovanillic acid, were increased in the limbic areas compared to the control group. In contrast, contents of 3,4-dihydroxyphenyl acetic acid were depleted significantly and dose dependently compared to the control group in the limbic areas of mice. In conclusion, natural cathinone has depleted motor coordination, accelerated anxiety in mice and altered the contents of dopamine and its metabolites.